Incidence of chronic Q fever and chronic fatigue syndrome: A 6 year follow‐up of a large Q fever outbreak. Issue 4 (22nd July 2021) - Ankert, Juliane; Frosinski, Janina; Weis, Sebastian; Boden, Katharina; Pletz, Mathias W.
Abstract: Acute Q fever is a generally self‐limiting infection caused by the intracellular gram‐negative bacterium Coxiella burnetii . For yet unknown reasons, a subset of patients develops chronic infection. Furthermore, chronic fatigue syndrome (CFS) as post‐acute Q fever sequelae has been described. We here investigated the rates of chronic Q fever and incidences of CFS 6 years after one of the largest European Q fever outbreaks that occurred in Jena, Germany in 2005 with 331 reported cases, who lived in proximity of a grazing flock of sheep. A total of 80 patients and their 52 non‐diseased household members from the former outbreak, were enrolled 6 years after the outbreak. Blood samples were collected and tested for chronic Q fever which was determined by seroprevalence using referenced immunofluorescence assays. Also, the presence of CFS was assessed using the Short Form Symptom Inventory developed by the Centers (United States) for Disease Control and Prevention (SF CDC‐ SI). In 80 out of 132 (60.6%) study participants, previous Q fever infection was confirmed serologically, while no previous infection was detected in the 52 household members. None of the participants fulfilled the serological criteria of chronic Q fever. The evaluation of the CDC‐SI did not show any differences between the two groups. Also, there was no difference between both groups regarding fulfillment of CFS‐defining criteria ( n = 3 (3.8%; sero‐positive) versus n = 2 (3.8%; sero‐negative), p = 0.655). Our 6‐year follow‐up study of a large Q fever outbreak did not find evidence of chronic Q fever or post Q fever CFS. There was no asymptomatic sero‐positivity in household members of Q fever patients.